Prediction of Separation Length of Turbulent Multiphase Flow Using Radiotracer and Computational Fluid Dynamics Simulation - S. Sugiharto; R. Kurniadi; Z. Abidin; Z. Stegowski; L. Furman (PPIKSN-BATAN, 2013)
Multiphase flow modeling presents great challenges due to its extreme importance in various industrial and environmental applications. In the present study, prediction of separation length of multiphase flow is examined experimentally by injection of two kinds of iodine-based radiotracer solutions into a hydrocarbon transport pipeline (HCT) having an inner diameter of 24 in (60,96 m). The main components of fluids in the pipeline are water 95%, crude oil 3% and gas 2%. A radiotracing experiment was carried out at the segment of pipe which is located far from branch points with assumptions that stratified flows in such segment were achieved. Two radiation detectors located at 80 and 100 m from injection point were used to generate residence time distribution (RTD) curve resulting from injection of radiotracer solutions. Multiphase computational fluid dynamics (CFD) simulations using Eulerian-Eulerian control volume and commercial CFD package Fluent 6.2 were employed to simulate separation length of multiphase flow. The results of study shows that the flow velocity of water is higher than the flow rate of crude oil in water-dominated system despite the higher density of water than the density of the crude oil. The separation length in multiphase flow predicted by Fluent mixture model is approximately 20 m, measured from injection point. This result confirms that the placement of the first radiation detector at the distance 80 m from the injection point was correct. Received: 04 December 2012; Revised: 29 January 2013; Accepted: 09 March 2013